"Save the country!" The protests of the National Rescue Movement of 2020 in Costa Rica - Chavarría, Stuart Daniel (2025)
Through the combination of the Analysis of the Situation (ADC) and the Analysis of Protest Events (AEP) this work focuses on understanding the dynamics of the mobilizations undertaken by the National Rescue Movement (MRN) during the period from July 22 to November 18, 2020. The analysis focuses on the first place in capturing the development of the situation from the main actors, events, scenarios and correlations of forces; and, on second place in reconstructing the day of mobilizations from the demanding actors, the defendant actors, the repertoires of action and the different demands. Among the main results, it concludes the emergence of a new actor with radical tendencies must be understood from the context of exception provided for by COVID-19.